تأثير اللولب على الموجودات التنظيرية والخلوية في عنق الرحم (Latakia University Journal -Medical Sciences Series, 2019)
أجري البحث في قسم التوليد وأمراض النساء بمشفى الأسد الجامعي, في الفترة بين 2/6/2009-2/5/2008. شمل البحث 178 مريضة, أجريت لهن لطاخة بابانيكولاو وتنظير مكبر لعنق الرحم, للتحري عن تأثير اللولب في الموجودات التنظيرية والخلوية في عنق الرحم.وتمت مقارنة النتائج لدى المريضات المستخدمات للوالب الرحمية (92) مريضة, مع مجموعة الشاهد من المريضات غير المستخدمات لأي من وسائل منع الحمل (86) مريضة. كما تمت دراسة تأثير كل من عوامل الخطورة المتعددة والمعروفة للإصابة بسرطان عنق الرحم على الموجودات التنظيرية لدينا. وتبين لدينا بالمقارنة بين المجموعتين وجود فرق بسيط في نسبة الموجودات التنظيرية الشاذة: فقد كانت النسبة في عينة مستخدمات اللوالب الرحمية =11.95% وفي العينة الشاهد النسبة=10.46%. وهذا يؤكد على استعمال اللولب بوصفه وسيلة آمنة وسهلة وفعالة لمنع الحمل, مع التأكيد على ضرورة الكشف الدوري باللطاخة والتنظير. This research was conducted in the Department of Obstetrics and Gynecology at Al-Assad University Hospital between 2/5/2008-2/6/2009. It included 178 patients admitted to Colposcopy and Papanicolaou smear to detect the effect of IUDs on colposcopic and cellular findings. The results of IUD users (92 patients) were compared to the control group (86 patients) who did not use any contraception. The effect of different risk factors related to cervix cancer on the colposcopic findings had also been studied. We found that there was a slight difference in the rate of abnormal colposcopic findings. This rate was 11.95% in the IUD users sample, and in the second was 10,46%. This ensured that IUD was a safe, easy, and effective means of contraception. stressing the importance of frequent Colposcopy and Papanicolaou smear tests.